2021
DOI: 10.1080/00207543.2020.1868597
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the adoption of blockchain technology in business supply chains: a total interpretive structural modelling (TISM) approach

Abstract: Blockchain is an emerging technology with a wide array of potential applications. This technology, which underpins cryptocurrency, provides an immutable, decentralised, and transparent distributed database of digital assets for use by firms in supply chains. However, not all firms are appropriately suited to adopt blockchain in the existing supply chain primarily due to their lack of knowledge on the benefits of this technology. Using Total Interpretive Structural Modelling (TISM) and Cross-Impact Matrix Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(87 citation statements)
references
References 87 publications
1
83
0
3
Order By: Relevance
“…The TISM approach has been extemsively applied in project management field (Sandbhor and Botre 2014 ; Wuni and Shen 2019 ). The TISM has been used in analysing the supply chain operational performance and challenges (Bag 2016 ; Agarwal and Seth 2021 ; Mathivathanan et al 2021 ). Also, the TISM has been used to analyzing Covid-19 challenges and impacts (Lakshmi Priyadarsini and Suresh 2020 ; Lakshmi Priyadarsini et al 2020 ; Sreenivasan and Suresh 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The TISM approach has been extemsively applied in project management field (Sandbhor and Botre 2014 ; Wuni and Shen 2019 ). The TISM has been used in analysing the supply chain operational performance and challenges (Bag 2016 ; Agarwal and Seth 2021 ; Mathivathanan et al 2021 ). Also, the TISM has been used to analyzing Covid-19 challenges and impacts (Lakshmi Priyadarsini and Suresh 2020 ; Lakshmi Priyadarsini et al 2020 ; Sreenivasan and Suresh 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, its nature is interpretative (Yadav et al, 2020 ). In addition, the ISM approach can investigate a variety of management situations through its ordered model description, but this approach has some disapprovals (Dwivedi & Madaan, 2020 ; Dwivedi et al, ( 2020 ); Mathivathanan et al, 2021 ). To conquer the short aspects of the ISM approach, an extended ‘TISM’ model was presented.…”
Section: Methodsmentioning
confidence: 99%
“…Next, MICMAC analysis is employed to classify the enablers based on their dependence and driving powers. This section of this study explains the methodology adopted from Mathivathanan et al (2021) and Shibin et al (2017) which is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%